2022
DOI: 10.3389/fnbeh.2022.859151
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Role of Vitamin D in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that can lead to severe social behavioral difficulties, which mainly manifests as social communication and interaction disorders; narrow interests; and repetitive, stereotyped behaviors. In recent years, the prevalence of ASD has increased annually, and it has evolved from a rare disease to one with a high incidence among childhood developmental disorders. The pathogenesis of ASD is considered to be the interaction of genetic and environmental fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 108 publications
(142 reference statements)
0
16
0
Order By: Relevance
“…An increase in oxidative stress and mitochondrial dysfunction can produce neural damage. Also, autistic disorder is associated with a deficiency in GABA neurotransmitters as well as serotonin and dopamine (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in oxidative stress and mitochondrial dysfunction can produce neural damage. Also, autistic disorder is associated with a deficiency in GABA neurotransmitters as well as serotonin and dopamine (37).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, administering vitamins D and E effectively improved rat function in rotarod, anxiety, and spatial learning tests. Vitamins D and E have powerful antioxidants (28,37), anti-inflammatory (41), and neurotransmitter regulatory effects (26,37). For the GABA inhibitory system, vitamin E creates a balance in activates of the enzymes converting glutamate to GABA in different brain regions (42); also, mice with vitamin D deficiency have shown a large decrease in GAD 65/67 expression in the whole brain.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is an active neurosteroid that plays a crucial neuroprotective role in the developing brain ( Ali et al, 2018 ). In particular, risk factors related to ASD—such as air pollution, cloudy weather, seasonal factors, and migration of dark-skinned immigrants to poleward latitudes—are all associated with vitamin D deficiency ( Wang et al, 2022 ). Current studies have found a low serum vitamin D level in children with ASD, which is negatively correlated with the symptoms of ASD children ( Guo et al, 2019 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is vast evidence supporting the relationship between vitamin D and ASD, including at the animal model, cellular, and physiological levels. However, there is still a lack of evidence from large-sample randomized controlled trials (RCTs), leading to a lack of consensus on the role of vitamin D in children with ASD ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, lower levels of vitamin D were reported in ASD children compared with neurotypical controls [ 12 , 13 , 14 ], and vitamin D supplementation was suggested to exert a potential beneficial effect in these children [ 15 ]. However, a clear consensus on the role of vitamin D in the pathogenesis of ASD has not been reached [ 16 ]. Different genes are involved in the vitamin D pathway, including (1) the vitamin D receptor ( VDR ) gene, a nuclear hormone receptor within the central nervous system [ 17 ]; (2) genes involved in the activation and degradation of vitamin D ( CYP2R1 , CYP27B1 , and CYP24A1 ) [ 18 ]; (3) the vitamin D binding protein ( DBP ) gene, which codifies for the protein that binds vitamin D metabolites in plasma [ 19 ].…”
Section: Introductionmentioning
confidence: 99%